Assessment of moisture resistance and bonding behavior of cup lump rubber modified asphalt mixture containing wax-based surfactant - Zainiah Mohd Zin; Mohd Rosli Mohd Hasan; Azura A Rashid; Muhammad Munsif Ahmad; Tracy Leh Xin Wong; Hui Yao (Materials Research Express)
The present study evaluates moisture induced damage potential using a sessile drop method and a pneumatic adhesion tensile testing instrument (PATTI). The bonding behavior of the aggregates (granite and limestone) and cup lump rubber modified asphalt binder (CMB) with wax-based surfactant (WS) was evaluated. The results revealed that the granite aggregate exhibited a higher work of adhesion compared to the limestone. In the dry condition, the addition of more than 0.15% WS to the CMB reduced the work of adhesion and the bonding strength. Using the sessile drop method, the moisture resistance of the limestone aggregate with the CMB and WS was enhanced, but the bonding strength was reduced. The incorporation of WS reduced the surface free energy (SFE) regardless of the aging conditions and made the aggregate surface more hydrophobic for the increased interfacial adhesion. Incorporating WS in the CMB improved the work of adhesion under the wet condition, thus indicating that WS is an effective anti-stripping agent. Considering its comprehensive properties in the CMB, the amount of WS should be limited to 0.15%.